Comparative Evaluation of Public and Private Financing in Determining the Company's Growth Strategy - Sonjaya, Yaya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study explores the comparative impact of public and private financing on corporate growth strategies, focusing on their respective advantages, limitations, and the contextual factors influencing their effectiveness. It further examines mixed financing strategies as a balanced approach to optimizing financial resources and operational flexibility in various industries. The research adopts a qualitative systematic literature review approach, synthesizing insights from recent studies across diverse theoretical and practical domains. It evaluates the interplay between public and private financing mechanisms, contextual influences such as macroeconomic conditions and industry dynamics, and the implications of mixed financing strategies. The study identifies that public financing provides substantial capital and market visibility, supporting large-scale expansion and diversification. However, it also imposes regulatory pressures and shareholder expectations. Private financing offers flexibility, strategic support, and greater managerial control, making it suitable for high-risk and innovative sectors, though it is limited by funding capacity and investor dependency. Mixed financing strategies are highlighted as a pragmatic solution, leveraging the strengths of both mechanisms to balance risk, cost, and flexibility. The study also emphasizes the critical role of external factors, such as economic stability, regulatory policies, and sector-specific needs, in shaping financing decisions. The findings offer practical recommendations for corporate leaders to align financing decisions with strategic objectives and for policymakers to create supportive regulatory frameworks and incentives. This dual approach fosters sustainable growth, innovation, and competitiveness across industries.